WEB Treatment of Intracranial Aneurysms: Clinical and Anatomic Results in the French Observatory - Pierot, L. (AJNR Am J Neuroradiol, 2016)
BACKGROUND AND PURPOSE: Flow disruption with the WEB device is a new technique for the endovascular treatment of wide-neck bifurcation aneurysms. To obtain precise data regarding the safety and efficacy of this treatment with high-quality methodology, the prospective French Observatory study was conducted. Analysis of these data is presented, including 1-year follow-up. MATERIALS AND METHODS: Patients with bifurcation aneurysms for which WEB treatment was indicated were included in this prospective, multicenter Good Clinical Practice study. Clinical data, including adverse events and clinical status at 1 month and 1 year, were collected and independently analyzed by a medical monitor. An independent core laboratory evaluated the anatomic results at 1 year following the procedure. RESULTS: Ten French neurointerventional centers included 62 patients (39 women), 33–74 years of age (mean, 56.6 ± 9.80 years) with 63 aneurysms. Aneurysm locations were the middle cerebral artery in 32 aneurysms (50.8%), anterior communicating artery in 16 (25.4%), basilar artery in 9 (14.3%), and internal carotid artery terminus in 6 (9.5%). Morbidity and mortality at 1 month were, respectively, 3.2% (2/62 patients) and 0.0% (0/62). Morbidity and mortality (unrelated to the treatment) at 1 year were, respectively, 0.0% (0/59) and 3.4% (2/59 patients). At 1 year, complete occlusion was observed in 30/58 aneurysms (51.7%); neck remnant, in 16/58 aneurysms (27.6%); and aneurysm remnant, in 12/58 aneurysms (20.7%). CONCLUSIONS: This prospective French Observatory study showed very good safety of aneurysm treatment with the WEB, with a high rate of adequate aneurysm occlusion at 1 year (79.3%).